2010
DOI: 10.1002/jsfa.3992
|View full text |Cite
|
Sign up to set email alerts
|

Value-added use of mushroom ergothioneine as a colour stabilizer in processed fish meats

Abstract: The results of this study clearly showed that ESH prepared from different mushroom species stabilized the colour of fish meats, and the extract from the F. velutipes was the most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…The extracts of several mushrooms containing ergothioneine (34) were also shown to prevent brown discoloration in processed fish meat (Bao et al, 2010b). Brown discoloration occurs when both deoxymyoglobin and oxymyoglobin are oxidized into metmyoglobin (metMb).…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…The extracts of several mushrooms containing ergothioneine (34) were also shown to prevent brown discoloration in processed fish meat (Bao et al, 2010b). Brown discoloration occurs when both deoxymyoglobin and oxymyoglobin are oxidized into metmyoglobin (metMb).…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…(2007) reported that the ESH content ranged between 210 and 2590 mg/kg −1 of dry weight in the most commonly consumed edible mushrooms in the United States. Bao et al. (2010a) determined that the ESH content of various mushrooms cultivated in Japan varied between trace amounts and 2080 mg/kg −1 of wet weight.…”
Section: Introductionmentioning
confidence: 99%
“…Flammulina velutipes is widely used as food or a food ingredient. A recent study revealed that the edible parts of F. velutipes contained a high amount of ESH compared to other cultivated mushrooms (Bao et al. , 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from tamogitake were prepared by the method of Bao et al (2010). The fruiting bodies of tamogitake were ground with a food processor and 50 g of the ground material was extracted with 250 ml water at 95°C in a glass round-bottom flask for 1 h. The supernatant was collected by centrifugation of the boiled mixture at 4°C and then evaporation at 40°C in vacuo.…”
Section: Preparation Of Crude Extracts From Tamogitakementioning
confidence: 99%